2007
DOI: 10.1186/1475-9292-6-5
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of Leishmania amazonensisstrains isolated in northeastern Brazil as revealed by DNA sequencing, PCR-based analyses and molecular karyotyping

Abstract: Background: Leishmania (Leishmania) amazonensis infection in man results in a clinical spectrum of disease manifestations ranging from cutaneous to mucosal or visceral involvement. In the present study, we have investigated the genetic variability of 18 L. amazonensis strains isolated in northeastern Brazil from patients with different clinical manifestations of leishmaniasis. Parasite DNA was analyzed by sequencing of the ITS flanking the 5.8 S subunit of the ribosomal RNA genes, by RAPD and SSR-PCR and by PF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 46 publications
2
30
0
Order By: Relevance
“…In terms of geographical distribution, Dorval et al (2006), Marlow et al (2013) and Carvalho et al (2013) reported its detection in Mato Grosso do Sul, Santa Catarina and Rio de Janeiro states, Brazil. Regarding clinical manifestations, Barral et al (1991) and Oliveira et al (2007) (FREITAS et al, 1989;LAINSON & SHAW, 1968;BRASIL, 2013). These vectors are less anthropophilic, which explains a lower frequency of human infection with this Leishmania species.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of geographical distribution, Dorval et al (2006), Marlow et al (2013) and Carvalho et al (2013) reported its detection in Mato Grosso do Sul, Santa Catarina and Rio de Janeiro states, Brazil. Regarding clinical manifestations, Barral et al (1991) and Oliveira et al (2007) (FREITAS et al, 1989;LAINSON & SHAW, 1968;BRASIL, 2013). These vectors are less anthropophilic, which explains a lower frequency of human infection with this Leishmania species.…”
Section: Discussionmentioning
confidence: 99%
“…The Leishmania isolate was obtained from a patient who presented diffuse form of CL in the state of Maranhão, Brazil. 19 The cells were maintained in alpha minimal essential medium (αMEM; Gibco ® ; Thermo Fisher Scientific, Waltham, MA, USA) supplemented with 10% inactivated fetal bovine serum (Multicell; Wisent Inc., St Bruno, QC, Canada), 100 μg/mL kanamycin (Sigma-Aldrich Co.), and 50 μg/mL ampicillin (SigmaAldrich Co.), and incubated at 24°C±1°C and pH 7.0 in BOD greenhouse (Model: 2005; Johns-VWR Scientific, Toronto, ON, Canada). The promastigotes were grown in cell culture flasks of 25 mL volume (Corning Incorporated, Corning, NY, USA) with an initial inoculum of 10 6 cells/mL and transferred to a new medium after reaching the stationary growth phase, twice a week.…”
Section: Animals and Parasitesmentioning
confidence: 99%
“…Smear and culture were positive. The Leishmania identified as Leishmania (Viannia) braziliensis was performed by Polymerase Chain Reaction (PCR), RFLP and sequencing of ribosomal DNA from region ITS1 [6]. The HIV serology was negative and the patient was not taking any immunosuppressant drugs.…”
Section: Case Reportmentioning
confidence: 99%